AERODYNAMIC DESIGN OF HIGH PRESSRE AXIAL FAN - Y. A. Ryzhov; S. A. Popov; H. Vu. Man (Научный вестник МГТУ ГА)
The paper presents the results of numerical studies of flow in a high axial fan of H-2, the geometric parameters are carefully designed by the author. The coefficients of performance, the total pressure, efficiency and capacity. Shows the benefits of fan of H-2 on several other fans, expressed in increased efficiency with equal dimensions and angles of blade setting.